Productivity growth in the Old and New Europe: the role of agglomeration externalities - Raffaele Paci; Emanuela Marrocu; Stefano Usai (European Regional Science Association (ERSA), 2011)
The recent history of Europe is characterized by a dual picture showing the Old and New countries in sharp contrast with respect to their industrial specialisation and economic performance. We aim at analyzing the intertwined performance of regions and industries in New and Old European economies by investigating the effects of local agglomeration externalities (mainly specialisation and diversity externalities) on total factor productivity dynamics. We also analyse the potential influence of regional intangible assets such as human and technological capital. The econometric analysis makes use of spatial econometric techniques to take into account the possibility of cross-border externalities.
Keywords: 330